Design and Development of a Web-Based Operational Information System for Culinary MSMEs Using Agile Scrum - M. Rudi Fanani; Nur Hadian; Nur Hayati (Universitas Islam Raden Rahmat, Malang, 2026)
In the era of digital transformation, Micro, Small, and Medium Enterprises (MSMEs) are increasingly encouraged to adopt operational digitalization to strengthen internal processes. This study aims to design and preliminarily evaluate an Agile Scrum-based operational information system intended to support internal efficiency in culinary MSMEs, particularly in transaction recording, processing speed, and inventory traceability. Prior to development, manual workflows showed slow transaction entry, inconsistent handwritten stock notes, and limited visibility for daily reconciliation—conditions used as qualitative baseline indicators for assessing potential efficiency improvements. The system was developed through three Agile Scrum sprints, with requirements gathered via observation and semi-structured interviews, modeled using Unified Modeling Language (UML), and evaluated through black-box functional testing and User Acceptance Testing (UAT). Black-box testing verified that core functions executed as intended, while early UAT feedback from five internal users produced an average satisfaction score of 86% on a Likert scale, indicating positive perceptions of usability, responsiveness, and reporting clarity. These findings represent preliminary perceptual evidence rather than demonstrated operational improvement, as no quantitative measurements—such as before–after transaction time, error rates, or reconciliation accuracy—were collected. Accordingly, the study does not claim proven efficiency gains but proposes an initial design that can be refined and empirically validated through future performance-based evaluations. The study contributes by positioning internal record-keeping digitalization as a practical entry point for MSME operational strengthening and by illustrating Scrum’s contextual applicability in resource-constrained business environments.